Use of the PowToon Online Presentation Application by Non-Digital Native Mathematics Teachers to Create Media and Apply it to the Learning Process - Dicky Fernanda J (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this research is to determine the perceptions of non-digital native mathematics teachers in the process of learning the PowToon application, to determine teachers' perceptions of the PowToon application in the process of creating learning media, and to determine students' perceptions of learning media created with the PowToon application by non-digital mathematics teachers. Methodology: This type of research is qualitative research. The research subjects were two non-digital native Mathematics teachers at Public High School 11 Jambi. To collect data, researchers used several instruments, including diaries, interview guides, and questionnaires. Diaries are used to collect personal notes and daily reflections from these teachers. An interview guide was used to conduct in-depth interviews with teachers to gain a deeper understanding of the use of digital technology. Meanwhile, the questionnaire was used to collect teacher responses to several questions related to the use of digital technology in learning. Main Findings: The research results seen from the teachers' diaries show that the perception of non-digital native mathematics teachers in the process of learning the PowToon application is positive. Meanwhile, the perceptions of non-digital native mathematics teachers were concluded based on interview data regarding the PowToon application in the process of creating positive learning media, and based on data processing analysis from 70 students who were the research sample, 12 students or 17.14% were in the very high category. 58 students or 82.85% were in the high category, and 10 students or 14.28% were in the medium category. Novelty/Originality of this study: This research provides an understanding of teachers' and students' perceptions of the use of the PowToon application in mathematics learning. These findings can provide guidance and input for non-digital native mathematics teachers in integrating digital technology in learning, as well as optimizing the use of the PowToon application as an effective and interesting learning media.